K.I.S.S. Lip Filler Technique - keeping injections simple and safe when filling lips - Vivian de Carvalho Amaral; Fernanda Aquino Cavallieri (Sociedade Brasileira de Dermatologia (SBD), 2023)
To simplify the procedure and increase lip augmentation safety, we have developed the KISS - Keep Injection Simple and Safe lip filler technique.To be simple, the method recommends only the evaluation of four anatomical parameters and the filling of five labial areas.To be safe, the injection is performed only in the supramuscular plane, using cannulas with a blunt tip, inserted in four entries: two in the upper lip and two in the lower lip. Fillers are injected in specific anatomical vectors for lips volumization, projection, contour improvement, and support of cupid's bow and lip corners.